Assessment of the role and mechanism of Bifidobacterium animalis subsp. lactis isolated from neonates' feces in protecting neonatal rats from Salmonella infection. (January 2023) - Lin, Yugui; Xie, Zhong; Li, Zhouyi; Yuan, Chunlei; Zhang, Chilun; Li, Yanfen; Xie, Kunke; Wang, Ke
Abstract: Objectives: It is now well known that Bifidobacterium animalis subsp. lactis ( B. lactis ), an important early-life colonizer of the gut, provides immune-related benefits to infants. The aim of the work is to explore the intraspecific resistance to Salmonella infection of B. lactis isolated from neonatal feces, and to learn more insights into how B. lactis mediates beneficial roles in early-life infection resistance. Methods: Five strains of B. lactis (NFBAL11/NFBAL23/NFBAL44/NFBAL63/NFBAL92) were screened from fecal samples of neonates born within fifteen days and pretreated neonatal rats prior to infection with Salmonella typhimurium ( S. typhimurium ) SL1344. The survival rate, fecal occult blood, diarrhea and hepatosplenomegaly were detected to assess the ability of B. lactis to prevent S. typhimurium infection. Furthermore, the structure of mucus layer, gene expression, cytokine levels, antioxidant levels and intestinal microflora composition were detected to explore the mechanism. Results: All strains showed activity against S. typhimurium, with B. lactis NFBAL23 being the most active, followed by NFBAL63 and NFBAL92. And these advantages weren't attained by enhancing physical growth and development. Mechanistically, the neonatal rats treated with B. lactis (NFBAL23/NFBAL63/NFBAL92) had improved intestinal barrier function involving physical, chemical, immune and biological barriers in the face of challenges posed by S. typhimurium . Conclusions: These findings revealed the intraspecific difference, beneficial roles and mechanisms of action of B. lactis against Salmonella infection early in life, which highlighted the necessity of supplementing appropriate B. lactis, and provided several potential B. lactis candidates for Salmonella infection treatment. Highlights: Strains of B. lactis isolated from neonates' feces were resistant to early-life Salmonella infection in significantly varying degrees. B. lactis isolates enhanced resistance against Salmonella by overall improving intestinal barriers. B. lactis NFBAL23 gained great potential as a neonatal anti- Salmonella agent.